IMPLEMENTASI KEBIJAKAN PENATAAN PEDAGANG KAKI LIMA PASCA PANDEMI COVID-19 DI KOTA MOJOKERTO - Jaya Agus Purwanto (Program Pascasarjana Universitas Wijaya Putra Surabaya, 2022)
The purpose of this study was to describe the implementation of the policy for structuring street vendors after the Covid-19 pandemic and the supporting and inhibiting factors in Mojokerto City. This type of research is a qualitative descriptive research with a policy research approach. The informants in this study consisted of the Department of Industry and Trade; Civil service police Unit; association of street vendors and traders. The results of the study show that Post-Covid-19 Pandemic Street Vendor Arrangement Policy in Mojokerto City is relatively good and according to the target. The supporting factors are the support of facilities and infrastructure, the cooperation of the person in charge and outreach and the Intensity of Supervision. While the inhibiting factor is the availability of land that is not able to simultaneously accommodate all street vendors, the arrangement budget that is not published is considered by street vendors to be not transparent and the lack of strict sanctions given to street vendors who violate.